CHANGE IN KNEE SEPARATION DISTANCE IN ADOLESCENT ATHLETES AFTER A 6-WEEK NEUROMUSCULAR TRAINING PROGRAM. Issue 7 (30th July 2021) - Gómez, Jorge E.; Wilson, P. Burke; Johnson, Timothy
Background: Existing neuromuscular injury prevention programs have relied principally on lower extremity strengthening, agility, cutting and landing technique to improve jump landing mechanics in order to prevent non-contact knee ligament injuries. Purpose: To determine whether a 6-week neuromuscular training program emphasizing core (back & hip) strengthening and dynamic balance exercises can significantly improve normalized knee separation distance (nKSD) during a standard counter-movement jump landing maneuver. Methods: Fourteen adolescent athletes (11 boys, 3 girls, ages 12-15) volunteered to undergo a 2 day/week, 6-week off-season training program. On the first day of training, the athletes underwent assessments that included 2 trials of a counter-movement jump from a 40cm platform. The tests were recorded using a video camera in the frontal plane. Using Dartfish motion analysis software, knee separation distance (KSD) was measured as the distance (cm) between the femoral condyles at the lowest point of the jump landing, and intertrochanteric distance (ITD) as the distance (cm) between the femoral trochanters. Normalized knee separation distance was computed as nKSD = KSD/ITD. The training program focused on three progressions; increasing difficulty of core strengthening exercises, balance exercises, and agility drills. One-hour training sessions were subdivided as follows; 5 min dynamic warm-up, 10 min stretching, 10 min body weight core exercises, 15 min balancing exercises, 10 min dumbbell core exercises, 15 minute agility drills, 5 min of rest/hydration breaks. The athletes repeated the counter-movement jump test at the end of the 6 weeks. Results: There was a significant improvement (t = 2.740, p = 0.017) in nKSD between post-test (0.789 + 0.372) and pre-test (0.683 + 0.323) Conclusion: A 6-week neuromuscular training program focused on core strengthening and balance significantly improved jump landing mechanics which may reduce the risk of knee ligament injury.